2023
DOI: 10.3390/membranes13030356
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Model Membranes Composed of Legionella gormanii Lipids

Abstract: Legionella gormanii is one of the species belonging to the genus Legionella, which causes atypical community-acquired pneumonia. The most important virulence factors that enable the bacteria to colonize the host organism are associated with the cell surface. Lipids building the cell envelope are crucial not only for the membrane integrity of L. gormanii but also by virtue of being a dynamic site of interactions between the pathogen and the metabolites supplied by its host. The utilization of exogenous choline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In addition, on the C −1 S − π plot, the minimum value more accurately identified the surface pressure at which the monolayer collapsed. The changes in the phospholipid composition caused by the choline presence in the medium for bacteria growth and their influence on the behavior of molecules on the subphase were thoroughly discussed in our previous paper [8]. In summary, the smaller lift-off areas of the π − A isotherms (Figure 4A,B, Table 1) for the PL+choline monolayers suggest that molecules are in closer proximity to each other in comparison to PL−choline.…”
Section: A'' B''mentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, on the C −1 S − π plot, the minimum value more accurately identified the surface pressure at which the monolayer collapsed. The changes in the phospholipid composition caused by the choline presence in the medium for bacteria growth and their influence on the behavior of molecules on the subphase were thoroughly discussed in our previous paper [8]. In summary, the smaller lift-off areas of the π − A isotherms (Figure 4A,B, Table 1) for the PL+choline monolayers suggest that molecules are in closer proximity to each other in comparison to PL−choline.…”
Section: A'' B''mentioning
confidence: 68%
“…The Brewster angle microscope images revealed that the monolayers formed from the lipids isolated from L. gormanii cultured in the medium with exogenous choline were more homogeneous than those formed from the lipids of bacteria cultured without the addition of exogenous choline. The monolayers of lipids extracted from bacteria cultured on the medium without the addition of choline displayed increased flexibility attributed to the presence of shorter chains (C14-C18) of unsaturated fatty acids, as well as a larger content of cardiolipin (21%), leading to the formation of heterogeneities (domains) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of LL-37's influence on single-class monolayers allows one to define which class mainly determines the susceptibility of multi-class model membranes to the peptide. The PE class constitutes 50% of the PL − choline mixture and 38% of PL + choline [9], and the results presented in this paper show that PE at 20 • C is the most susceptible to LL-37 incorporation out of all the analyzed classes. In consequence, it can be assumed that PE's behavior in the presence of the peptide is decisive for the peptide-mixture interactions and defines the 25% and 18% mean molecular area increase registered for PL − choline and PL + choline, respectively [17].…”
Section: Discussionmentioning
confidence: 56%
“…The peptide embedding observed in our studies is more pronounced for less densely packed PE − choline (Figure 2, Table S1) in comparison to PE + choline. The expansion of the PE − choline monolayers can be associated with a greater content of cyclopropane acid c17:0 [9]. The presence of a cyclopropane ring structure increases the spacing between hydrocarbon chains by reducing their ability to pack tightly due to the weakening of the Lifshitz-van der Waals forces that stabilize chain-chain interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation